A cosmopolitan, Sami-friendly scholar? Väinö Tanner on the best way to treat the Sami - Nyyssönen, Jukka (Northern Arctic Federal University, 2016)
The topic of this article is Väinö Tanner’s views on Sami policies, which are searched from numerous contexts, including his personal career and Nordic Sami policies. Also the discur-sive resources, which he re-produced, are charted. Of the contemporaneous Sami policies, he ad-vocated the Swedish variant, which suited better his agendas in his scholarly production on the Skolt Sami. The origin of the choice can be located in a longer professional contact with Swedish experts on the Sami and the expert-role provided by the Swedish discourses of the Sami. The anti-Finnish agendas in his scholarly production and the consequent wish to lift the Sami in the timely hierarchies turned the more aggressive Norwegian rhetoric on the Sami as unusable. In addition, he showed signs of a cultural sensitivity, which turned him suspicious of assimilative policies.